The International Migration Flow of Labor During the Process of Integration of the Republic of Moldova with the European Union - Alic Birca (CES Working Papers, 2015)
In this article the author debates the international migration flow of labor during the process of Republic of Moldova's integration with the European Union. Therefore, the author presents the economic causes and effects of the international migration of workforce. Both emigration and immigration flows grouped by specific categories of persons are presented. The evolution of the number of Moldovan immigrants and emigrants in the member states is also presented. Furthermore, the article shows statistic data regarding the number of Moldovan citizens aged over 15 that are working abroad or searching for a workplace abroad.
Keywords: F15; F16; F22; J61; 330; migration; workforce; international migration; emigrant; immigrant